The Effect of the Winner's Curse Phenomenon in Low Balling on the Auditor's Effort in Performing the Audit Tasks Using Game Theory - Tabandeh Salehi (University of Tehran, 2021)
Objective: Low balling is one of the major challenges of the auditing profession. Low balling can be unintentional (the phenomenon of the winning curse) or consciously as intentional behavior to enjoy future benefits. The present study focuses on the winner's curse phenomenon. The purpose of this study is to investigate the effect of the winner’s curse phenomenon in low balling on the auditor's efforts in performing the audit tasks. Methods: This study done using laboratory method and game theory. 115 people participated in the games in year 2020 using the sampling method of available sample from the statistical population of accounting students of Shahid Bahonar University of Kerman. The first game is in the simple conditions of the audit market and the second game is an audit market with complex conditions that theoretically include important features of the audit services market. These games were programmed in Z-Tree software. At the time of data collection, due to the specific conditions of Covid-19 disease and the Impossibility of attendance of participants in the laboratory, from the virtual method was used. In this way, using Oracle VM Virtual Box, FileZilla Client and Zunleashed software, links were sent to the participants and they entered the lab space without the need for any special software and just by clicking on these links. Results: The results showed that auditors in both markets, on average, offer prices less than the Risk Neutral Nash Equilibrium. These results are evidence of the existence of the winner's curse phenomenon in the market of auditing services. In addition, the number and extent of this phenomenon in complex conditions of the audit market is greater than the simple conditions of the audit market. Also this study shows auditors who face unexpected losses from the winner’s curse are looking for an opportunity to recoup loss, and therefore, they decide to reduce their efforts to perform audit tasks. Plus, the present study aimed to compare the theory of expected utility and mental accounting showed that mental accounting can be a correct explanation for the behavior of auditors when face the winner's curse phenomenon. The results also showed, the auditors whose under performance was identified and were fined for it, less likely to reduce their efforts in subsequent periods. Auditors, whose underperformance was not identified and who were not fined, are more likely to reduce their efforts in subsequent periods. Conclusion: The results showed that uncertainty in the cost of the audit leads to low-balling due to the occurrence of the winner's curse phenomenon and this source of low-balling threatens the quality of the audit. But when auditors experience penalties for low quality in previous periods, the quality of the audit improves.